Professionally-Oriented Communication Styles of Social Pedagogues: A Review - Tetiana Savchenko (Centre for Behaviour and Wellness Advocacy, 2016)
Communication is important in all human endeavours. This article evaluates the concept of "style" - in a professional setting. This paper comprehensively examines, the "individual style of communication", the "style of pedagogical communication" and the "social pedagogues' professionally-oriented communication style". It also examines the essence of an individual style of professionally-oriented communication among social pedagogues. The main focus of this paper concentrates scientists' views regarding the characteristics of each communication style. Finally, the major professionally-oriented communication styles within the spectrum of social pedagogues were similarly analyzed. An effective individual style of productive communication is the best style of professionally-oriented communication among social pedagogues